Healthcare organizations and Ethics - Petralia, Paolo; Doldi, Marco (Medicina e Morale, 2024)
To humanize healthcare management means recognizing the instrumental value of economics in relation to human care and patient assistance, and embracing the principle of ethical responsibility as the most suitable means to reconcile two seemingly irreconcilable aspects of healthcare organizations: on one hand, the concept of an organization focused on achieving economic efficiency, and on the other, an organization committed to satisfying care relationships and needs while disregarding the appropriate and efficient use of increasingly scarce resources. Therefore, we must immediately bring ethics to the decision-making table, adopting a transdisciplinary approach. By doing so, we may, while addressing new challenges, return to timeless principles, offering meaningful responses and building a pathway to redefine decisions for the future within a framework of sustainability, universalism, and equity.